New One-Pot Synthesis of 1,3,5-Triazines: Three-Component Condensation, Dimroth Rearrangement, and Dehydrogenative Aromatization - Ahmad Junaid,; Lim, Felicia Phei Lin; Tiekink, Edward R. T. *; Dolzhenko, Anton V (American Chemical Society, 2019)
A new, eﬀective one-pot synthesis of the 6,N2-diaryl-1,3,5-triazine-2,4-diamines under microwave irradiation was developed. The method involved an initial three-component condensation of cyanoguanidine, aromatic aldehydes, and arylamines in the presence of hydrochloric acid. Without isolation, the resulting 1,6-diaryl-1,6-dihydro-1,3,5-triazine-2,4diamines were treated with a base to initiate Dimroth rearrangement and spontaneous dehydrogenative aromatization, aﬀording the desired compounds. The developed method was found to be suﬃciently general in scope, tolerating various aromatic aldehydes and amines; by using their combinations in the ﬁrst step, a representative library of 110 compounds was successfully prepared and screened for anticancer properties.